Signaling Through gp130 Compromises Suppressive Function in Human FOXP3+ Regulatory T Cells - Bin Dhuban, Khalid; Bartolucci, Sabrina; d'Hennezel, Eva; Piccirillo, Ciriaco A. (Frontiers in Immunology, 2019)
The CD4+FOXP3+ regulatory T cell (Treg) subset is an indispensable mediator of immune tolerance. While high and stable expression of the transcription factor FOXP3 is considered a hallmark feature of Treg cells, our previous studies have demonstrated that the human FOXP3+ subset is functionally heterogeneous, whereby a sizeable proportion of FOXP3+ cells in healthy individuals have a diminished capacity to suppress the proliferation and cytokine production of responder cells. Notably, these non-suppressive cells are indistinguishable from suppressive Treg cells using conventional markers of human Treg. Here we investigate potential factors that underlie loss of suppressive function in human Treg cells. We show that high expression of the IL-6 family cytokine receptor subunit gp130 identifies Treg cells with reduced suppressive capacity ex vivo and in primary FOXP3+ clones. We further show that two gp130-signaling cytokines, IL-6 and IL-27, impair the suppressive capacity of human Treg cells. Finally, we show that gp130 signaling reduces the expression of the transcription factor Helios, whose expression is essential for stable Treg function. These results highlight the role of gp130 in regulating human Treg function, and suggest that modulation of gp130 signaling may serve as a potential avenue for the therapeutic manipulation of human Treg function.